A novel cyano functionalized silica-titania oxide sol-gel based ionic liquid for the extraction of hazardous chlorophenols from aqueous environments - Bakhshaei, S.; Kamboh, M.A.; Mohamad, Sharifah; Zain, Sharifuddin Md; Ma'amor, Azman (Royal Society of Chemistry, 2016)
In the present investigation a cyano functionalized silica-titania oxide sol-gel based ionic liquid (Si-Ti@CN/IL) has been successfully synthesised via sol-gel immobilization of cyanopropyltriethoxysilane and 1-benzyl-3-(trimethoxysilylpropyl)imidazolium chloride ionic liquid (BTMP-IM) on the silica-titania mixed oxide surface. The newly prepared Si-Ti@CN/IL was used as an adsorbent for the separation/preconcentration of chlorophenols from water samples prior to their HPLC-UV determination. Synthesis of Si-Ti@CN/IL was confirmed by Fourier transform infrared (FT-IR) spectroscopy, field emission scanning electron microscopy (FESEM), Brunauer-Emmett-Teller (BET), thermo gravimetric analysis (TGA), X-ray diffraction (XRD) and elemental (CHNS) analysis. During the extraction process, various kinds of interactions such as π-π interactions and hydrogen bonding between the anionic/cationic sites were monitored. The extraction of chlorophenols on Si-Ti@CN/IL is highly pH dependent and a significant percent extraction was achieved at pH = 2. The Si-Ti@CN/IL provided low limit of detection (LOD = 0.83-0.95 μg L-1) with a linearity range from 10-1000 μg L-1 (LOQ = 2.77-3.17 μg L-1). The field studies with high recovery (73.39-105.54%) as well as acceptable precision (%RSD 0.82-4.19) also supported the effectiveness of Si-Ti@CN/IL, which could be useful for the extraction of selected chlorophenols from tap water, lake water and leachate from landfill sites. The comparative data support Si-Ti@CN/IL as an effective extractant for selected chlorophenols.